To Compare Effect of Dual Task Training on Treadmil V/S Conventional Balance Exercises on Balance and Risk of Fall in the Elderly Community Dwellers - Lai Pathak (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and Aims This study is to see how effective dual task training on treadmill on balance and risk of fall is and to compare its effectiveness with conventional balance exercises. In geriatric population, balance is the most commonly affected due to age related changes in the brain. Also they experience falls or build fear for it due lack of coordination and strength, therefore, loss of balance. Since dual task on treadmill will help in improving co-ordination as motor and cognitive tasks are involved, it can be used to improve balance. As doing our daily chores includes dual tasking every time, following study is undertaken on geriatric population as they are most prone for falls. Method A comparative study was done on 30 individuals of Talegaon Dabhade (age 65 and above) which were divided into two groups by simple random sampling. In experimental group 15 individuals were given dual task training on treadmill for 6 weeks in 18 sessions (3times/week). The control group of 15 individual was given conventional balance exercise. Pre and post outcome measures were taken on BBS, DGI and MFES. Results The scores increased more in experimental group than control group in BBS with p value of 0.0293, in DGI p value of 0.0001 and in MFES p value of 0.0285 which are statistically significant. Therefore, in this study we can say that dual task training on treadmill is more effective than balance exercises.